2020
DOI: 10.20546/ijcmas.2020.911.286
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Heritability and Genetic Advance for Yield and Yield Attributes in Tomato (Solanum lycopersicum L.)

Abstract: The magnitude of variability and its genetic components are the most pivotal aspects of breeding material. Variability in tomato is anticipated to be immense as the fruits vary greatly in shape and size (Dixit and Dubey, 1985;Bhardwaj and Sharma, 2005). Studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
8
7
0
Order By: Relevance
“…In the present investigation high (>20%) genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were observed for the traits viz., number of primary branches per plant, fruit length, fruit width, fruit shape index, pericarp thickness, lycopene content, average fruit weight, fruit yield per plant and fruit yield per m 2 in the both segregating population of Cheramy RZ-F 1 and Sheeja derived F 2 population. These results are in accordance with Hazim et al (2017) [16] , Mamatha et al (2017) [27] , Rakesh et al (2018) [37] , Reddy et al (2019) [41] and Anuradha et al (2020) [5] . It indicates existence of broad genetic base, which would be amenable for further selection.…”
Section: Variability Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…In the present investigation high (>20%) genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were observed for the traits viz., number of primary branches per plant, fruit length, fruit width, fruit shape index, pericarp thickness, lycopene content, average fruit weight, fruit yield per plant and fruit yield per m 2 in the both segregating population of Cheramy RZ-F 1 and Sheeja derived F 2 population. These results are in accordance with Hazim et al (2017) [16] , Mamatha et al (2017) [27] , Rakesh et al (2018) [37] , Reddy et al (2019) [41] and Anuradha et al (2020) [5] . It indicates existence of broad genetic base, which would be amenable for further selection.…”
Section: Variability Studiessupporting
confidence: 90%
“…Heritability was calculated according to Weber and Moorty (1952) [56] and genetic advance as per cent of mean was estimated using the method of Johanson et al (1955). Genotypic and phenotypic correlations were calculated as per Al-Jibouri et al (1958) [5] . The direct and indirect paths were obtained according to the method of Dewey and Lu (1959) [11] .…”
Section: Discussionmentioning
confidence: 99%
“… Javed et al (2022) studied the higher PCV and GCV for yield and yield-related traits in tomato hybrids and indicated the role of genetic variability in plant selection. Understanding the nature of the inherited trait of tomatoes, whether they are phenotypic or genotypic, is essential ( Anuradha et al, 2020 ). Erazo et al (2020) investigated the higher h 2 coupled with higher genetic advance for the number of fruits per cluster (NFRC) and single fruit weight (SFW) (g).…”
Section: Introductionmentioning
confidence: 99%
“…[18] in rice, Reddy and Shanthi (2013) [17] , PoteKar et al (2014) [13] , Janghel et al (2018) [7] in musk melon for average fruit weight; Reddy and Shanthi (2013) [17] , PoteKar et al (2014) [13] in musk melon for fruit yield per vine and Srivastava et al 2019a,b [21,22] in Brinjal. [20] in Brinjal, Ravali et al, 2017 [16] , Triveni et al, 2017 [24] , Somraj et al, 2017 [19] , Naveen et al, 2018 [9] , Chandrashekhar et al, 2018 [5] , Rajashekar Reddy et al, 2017 [15] , 2019, Pidigam et al, 2019 [12] , Anuradha et al, 2020 [2] , while, Reddy and Shanthi (2013) [17] reported low to moderate heritability for certain characters in muskmelon. High heritability in broad sense indicated that large proportion of phenotypic variance was attributable to the genotypic variance and were less influenced by environment.…”
Section: Resultsmentioning
confidence: 99%